“I Teach Character in My Class”: Integrating Character Education in EFL Reading Classroom at Islamic Higher Education - Siti Nuraeni Muhtar; Dahlya Indra Nurwanti; R. Nadia R. P. Dalimunthe (Jurnal Pendidikan Islam, 2018)
This article explores teacher's experiences and students' perceptions of character and values education at the university level. This is a case study of how teacher integrates character education in EFL Reading Comprehension subject at Islamic higher education context. The data from ten students and a teacher are collected through an online interview and questionnaires. The result showed the characters implied in EFL Reading Comprehension Subject are eleven characters include learning method, critical thinking, independence, creativity, courage/self-confidence, communicativeness, responsibility, honesty, religiousness, cooperation, tolerance. Those characters are positively responded by the students in their learning process in the classroom. Besides, the teacher also integrated those values in the teaching and learning process to instill students' character education.